Effect Of Accounting Conservatism In Financial Performance Industries In The Financial Sector Registered In Indonesia Stock Exchange - Farah Margaretha Leon; Sony Hendrawan (Indonesian Management and Accounting Research, 2017)
The problems discussed in this research is to examine the effect of accounting conservatism and firm size on financial performance indicators as measured by return on assets (ROA), earnings per share (EPS) and market price of shares in companies engaged in the financial sector listed in the Indonesia Stock Exchange / Bursa Efek Indonesia (BEI). The purpose of this study is to examine the assumptions of the influence of accounting conservatism and firm size on financial performance indicators as measured by return on assets (ROA), earnings per share (EPS) and market price of shares in companies that engaged in the financial sector listed on the Bursa Efek Indonesia (BEI). The method of analysis of this study using multiple linear analyses with the number of samples of 61 companies engaged in the financial sector listed on the stock exchange of Bursa Efek Indonesia (BEI). The results of this study indicate that accounting conservatism has a significant influence on earnings per share (EPS) and market price of legitimate companies in the financial sector, but accounting conservatism has no significant effect on return on assets (ROA). The implications of this study are beneficial to investors who use information as a reference before investing that firm size and accounting conservatism policies in corporate financial reporting can increase the rate of return on investment. As for corporate management to improve the level of accounting conservatism policy in financial reporting so that the earning per share (EPS) and stock market prices may increase.